WORKSHOP PENINGKATAN LITERASI DATA SISWA MELALUI PEMBELAJARAN BERBASIS PROYEK DIGITAL DI SMP KRISTEN SATYA WACANA SALATIGA - Adi Setiawan; Faldy Tita; Lennox Larwuy; Amazia Ananta Prabaswara; Harfeley Leipary; Daniel Bramantyo Ranu Bagaskoro (Jurnal Abdi Insani, 2026)
The development of the digital era demands data literacy skills as a basic 21st-century skill that is important for junior high school students. Based on observations at SMPK Satya Wacana Salatiga, most students still experience difficulties in understanding, interpreting, and using data in learning. This community service activity aims to improve students' data literacy through hands-on practice-based training with an interactive and contextual learning approach. The implementation method includes socialization, data concept training, data processing simulations using spreadsheets and R software, and evaluation through pre-tests and post-tests. The results showed a significant increase in data analysis skills. The average pre-test score of 3.11 increased to 3.84 in the post-test, with an average normalized gain (K) of 0.40, which is included in the medium category. The paired t-test produced a value of t = -12.49 and p-value = 0.000 (p-value < 0.05), indicating a significant difference between the results before and after the training. A total of 44 students were in the medium improvement category, 38 students were low, and 19 students were high. These findings indicate that R-based data literacy training is effective in improving junior high school students' conceptual understanding, self-confidence, and analytical skills, and is relevant to be developed as a 21st-century learning model.